Effectiveness of Behavioral Counseling Model of Modeling Techniques for Developing Self Exhibition - Putra, Gusti Agung aditya Nata; Dharsana, I Ketut; Darmayanti, Ari (Department of Guidance and Counseling, FIP, Undiksha, 2017)
This research conducted at SMA LAB Undiksha Singaraja. The type that is